Social Integration of North Korean Refugees through Sport in South Korea. Issue 12 (13th August 2017) - Park, Kyoungho; Ok, Gwang
Abstract: South and North Koreans, separated for more than 60 years since the Korean War, show marked sociocultural differences despite their shared ethnicity. North Korean residents, who are isolated from international society and struggle to survive amid severe food shortages, sometimes seek to escape the country. In this study, how sports institutions contribute to the social unity of South Korea through the re-socialization of North Korean refugees who escaped life-or-death situations to enter South Korea is explored, along with changes in these institutions over time. Sports programmes have been implemented at Hanawon, where North Korean refugees are educated as members of South Korean society, to promote mutual friendship and help refugees recover from health problems that developed. Social sports programmes aimed at North Korean refugees have been used as a mechanism to overcome cultural foreignness and restore social unity. Corporate sports programmes for North Korean refugees have been implemented to aid in their self-realization and to create economic added value. These results show that sport can be an important cultural tool to reinforce national identity. It is argued that the social integration of North Korean refugees in South Korea, which is often called early-arrived unification, can be successfully realized through sport.